The immune factors involved in the rapid clearance of bacteria from the midgut of the tick Ixodes ricinus - Guizzo, Melina Garcia; Frantová, Helena; Lu, Stephen; Kozelková, Tereza; Číhalová, Kristýna; Dyčka, Filip; Hrbatová, Alena; Tonk-Rügen, Miray; Perner, Jan; Ribeiro, José M.; Fogaça, Andrea C.; Zurek, Ludek; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
Ticks are obligate hematophagous arthropods that transmit a wide range of pathogens to humans as well as wild and domestic animals. They also harbor a non-pathogenic microbiota, although our previous study has shown that the diverse bacterial microbiome in the midgut of Ixodes ricinus is quantitatively poor and lacks a core. In artificial infections by capillary feeding of ticks with two model bacteria (Gram-positive Micrococcus luteus and Gram-negative Pantoea sp.), rapid clearance of these microbes from the midgut was observed, indicating the presence of active immune mechanisms in this organ. In the current study, RNA-seq analysis was performed on the midgut of I. ricinus females inoculated with either M. luteus or Pantoea sp. or with sterile water as a control. While no immune-related transcripts were upregulated by microbial inoculation compared to that of the sterile control, capillary feeding itself triggered dramatic transcriptional changes in the tick midgut. Manual curation of the transcriptome from the midgut of unfed I. ricinus females, complemented by the proteomic analysis, revealed the presence of several constitutively expressed putative antimicrobial peptides (AMPs) that are independent of microbial stimulation and are referred to here as ‘guard’ AMPs. These included two types of midgut-specific defensins, two different domesticated amidase effector 2 (Dae2), microplusin/ricinusin-related molecules, two lysozymes, and two gamma interferon-inducible lysosomal thiol reductases (GILTs). The in vitro antimicrobial activity assays of two synthetic mature defensins, defensin 1 and defensin 8, confirmed their specificity against Gram-positive bacteria showing exceptional potency to inhibit the growth of M. luteus at nanomolar concentrations. The antimicrobial activity of midgut defensins is likely part of a multicomponent system responsible for the rapid clearance of bacteria in the tick midgut. Further studies are needed to evaluate the role of other identified ‘guard’ AMPs in controlling microorganisms entering the tick midgut.